A Study on Challenges & Issues in Implementing HR Strategies at Organisations in Indian Context - Dr. Rajesh K. Pandey; Sonali Kinjale; Nishi Tamboli (International Journal of Engineering and Management Research, 2023)
HR Management at Organisations is mammoth task and it requires utmost strategizing. The HR Strategies do take efforts and an insightful strategy will have long lasting impact. The HR Strategy Implementation does have its own share of challenges. The Challenges may range from the Management end of the Organisation till the Employees end while accepting & implementing the strategy. Efforts have been taken by every organisation to mitigate the challenges however the journey of remedy & actions takes its own strategic time. A well defined HR Strategy backed by a proper implementation has the best potential to reap the benefits for the Organisations. This paper is an Exploratory & Descriptive study conducted with the help of massively secondary data and Primary Data in the form of Interview Method. The Authors have Interviewed 5 Industry representatives to collect the view points on the theme of the study. The study aims to understand the significance of HR Strategies for the Organisations. It further aims to study the Challenges & issues in implementing HR Strategies at Organisations. The authors have gathered the inferences from the Interviews of the HR Managers of selected Organisations pertaining to the HR Strategies implementation at their respective organisations. The scope of the study comprises of the thoughtful review of theoretical data pertaining to the HR Strategies, issues and Challenges in implementing the Strategies. The Authors have considered the Organisations at large rather any specific sector or region; hence this may be a limitation of the study as the inferences are indicative in nature rather exhaustive. HR Strategies shall certainly attract issues & challenges, the success lies in defining the Strategies properly & implementing the same strategically.